Quantum Erasure Cryptography - Salih, Hatim (Frontiers in Physics, 2016)
The phenomenon of quantum erasure has long intrigued physicists, but has surprisingly found limited practical application. Here, we propose a protocol for quantum key distribution (QKD) based on quantum erasure, promising inherent security against detector attacks. We particularly demonstrate its security against a powerful detector-blinding attack.